2020
DOI: 10.7150/ijms.48128
|View full text |Cite
|
Sign up to set email alerts
|

The exploration of Hashimoto's Thyroiditis related miscarriage for better treatment modalities

Abstract: Hashimoto's thyroiditis (HT) is the most prevalent autoimmune thyroid disease (ATD) worldwide and is strongly associated with miscarriage and even recurrent miscarriage (RM). Moreover, with a deepening understanding, emerging evidence has shown that immune dysfunctions caused by HT conditions, including imbalanced subsets of CD4+ T-helper cells, B regulatory (Breg) cells, high expression levels of CD56dim natural killer (NK) cells, and cytokines, possibly play an important role in impairing maternal tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 191 publications
(251 reference statements)
0
14
0
1
Order By: Relevance
“…Our previous study demonstrated that treatment with levothyroxine did not reduce the miscarriage rates or increase the clinical pregnancy and live birth rates of women undergoing IVF-ET who had normal thyroid function and tested positive for thyroid autoantibodies [ 26 ]. Dysfunctions in immunological regulation may be involved in the mechanism and should be explored further [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that treatment with levothyroxine did not reduce the miscarriage rates or increase the clinical pregnancy and live birth rates of women undergoing IVF-ET who had normal thyroid function and tested positive for thyroid autoantibodies [ 26 ]. Dysfunctions in immunological regulation may be involved in the mechanism and should be explored further [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a range of works 13,21,30,31 , especially retrospective study, have determined a high concurrence rate of HT and PTC from surgical specimens but the relationship between these two diseases, as well as HT and CLNM, has been controversial. Immunologically, emerging evidence has shown that an abnormal in ammatory response, especially the imbalanced subsets of T cells, NK cells, and cytokines were presenting in HT condition 12,32 , which could potentially affect the tumor microenvironment and subsequent prognosis. For instance, in vitro experiment, Lubin et al 33 conducted that the presence of background HT was contributed to a higher risk of CLNM via increased programmed death ligand-1(PD-L1).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal AITD may also be an independent risk factor for newborn hospitalisation in the intensive care unit [124]. The reasons for the increased risk of obstetric failure in euthyroid women are still not clearly understood, and they include direct adverse effects of aTPO antibodies (including cross-reactions between aTPO antibodies and hCG in accessing the hCG receptor), decreased thyroid and ovarian reserve, older age of patients with Hashimoto's disease, coexistence of other autoimmune diseases, and immunological disturbances in the course of autoimmune diseases (including increased concentrations of endometrial cytokines) [125,126].…”
Section: Anti-thyroid Antibodies -Effects On Procreationmentioning
confidence: 99%
“…Przyczyn wzrostu ryzyka niepowodzeń położniczych u kobiet z AITD w okresie eutyreozy wciąż jednoznacznie nie poznano. Postuluje się między innymi bezpośredni, niekorzystny wpływ przeciwciał aTPO (w tym reakcje krzyżowe pomiędzy przeciwciałami aTPO i hCG, w dostępie do receptora dla hCG), zmniejszoną rezerwę tarczycową oraz jajnikową, starszy wiek pacjentek z chorobą Hashimoto, współwystępowanie innych chorób autoimmunizacyjnych oraz zaburzenia immunologiczne w przebiegu chorób z autoagresji (w tym zwiększony poziom cytokin endometrialnych) [125,126].…”
Section: Guidelinesunclassified